Risk Factors for Thrombosis in an African Population. Issue 7 (January 2014) - Fall, Awa O.T.; Proulle, Valérie; Sail, Abibatou; Mbaye, Alassane; Ba, Pape Samba; Diao, Maboury; Seck, Moussa; Gadji, Macoura; Gning, Sara B.; Diop, Saliou; Dièye, Tandakha N.D.; Faye, Blaise Félix; et al.
Little is known about the biological, epidemiological, and clinical risk factors for thrombosis and venous thromboembolism (VTE) among Black Africans. We undertook a study of the prevalence of VTE risk factors for thrombosis in a Senegalese population. A three-year cross-sectional and case-control study involving 105 cases and 200 controls was conducted in various hospitals in Dakar (Senegal). Our results demonstrate that oral contraception, immobilization by casts, surgery, and blood group were significantly associated with VTE occurrence. Additionally, 16 cases and 2 controls had protein S (PS) values of less than 48.4% (M-2SD), exhibiting a highly significant difference ( P < 1 x 10 −4 ). The number of cases with a low protein C (PC) level was significantly higher than the respective number of controls. Using logistic regression methods, we established a correlation between significantly associated variables and deep venous thrombosis (DVT) occurrence. Age, obesity, sickle cell disease, and PC deficiency were not significantly associated with thrombosis. In contrast, gender, PS deficiency, varicose veins, surgery, non-O blood type, and the presence of anti-phospholipid antibodies were significantly and independently associated with DVT. These findings are extremely useful for clinical management of patients suffering from DVT and can help to reduce the high recurrence rate observed in our study.